Periodontitis contributes to aberrant metabolism in type 2 diabetes mellitus rats by stimulating the expression of adipokines. (12th October 2015) - Luo, S.; Yang, X.; Wang, D.; Ni, J.; Wu, J.; Xu, Z.; Xuan, D.; Zhang, J.
Abstract : Background: Periodontitis has been associated with type 2 diabetes mellitus. We investigated the effects of local aberrant secretion of adipokines in diabetic rats on systemic metabolism. Material and Methods: Otsuka Long‐Evans Tokushima Fatty (OLETF) and non‐diabetic Long‐Evans Tokushima Otsuka rats were used as a diabetic model and associated control, respectively. Periodontitis was induced using a silk ligature for 36 wk. Rats were grouped into OLETF with (OP+) or without (OP−) periodontitis and Long‐Evans Tokushima Otsuka with (LP+) or without (LP−) periodontitis. Alveolar bone resorption and destruction were evaluated by micro‐computed tomography and hematoxylin and eosin staining. After 20 wk of periodontitis induction, lipids, insulin, interleukin‐1, leptin and plasminogen activator inhibitor‐1 were analyzed, and mRNA expressions of NF‐κB, Mark8, TLR2 and ‐ 4, IKBKB and Nampt were evaluated by quantitative polymerase chain reaction in adipose tissue. Results: After ligation, OLETF rats exhibited typical periodontitis lesions with the clinical features of type 2 diabetes mellitus. When compared with the OP(−) group, the area under curve of the oral glucose tolerance test and homeostatic model assessment–insulin resistance values were significantly higher in the OP(+) group. Micro‐computed tomography showed that the OP(+) group had more bone resorption than the OP(−) group. When compared with the OP(−) group, the OP(+) group also exhibited higher total cholesterol ( p < 0.05), leptin ( p < 0.05), insulin ( p > 0.05) and higher expression of Nampt ( p < 0.05) and IKBKB ( p < 0.05). The LP(+) group had a trend towards higher bone resorption when compared with the LP(−) group. Additionally, no difference in white adipose tissues or adipokines was found between LP(+) and LP(−) rats. Conclusions: Chronic periodontitis can alter lipid profiles in affected rats, elevate adipose tissue expression of Nampt and affect the metabolism of adipose tissue through the NF‐κB pathway to inflame diabetes.